NPY Receptor 2 Mediates NPY Antidepressant Effect in the mPFC of LPS Rat by Suppressing NLRP3 Signaling Pathway - Wenjiao Wang; Tao Xu; Xinyue Chen; Kemeng Dong; Chunkai Du; Jing Sun; Cuige Shi; Xiaoxiao Li; Yutao Yang; Hui Li; Zhi-Qing David Xu (Mediators of Inflammation)
Accumulated evidences show that neuroinflammation play a pivotal role in the pathogenesis of depression. Neuropeptide Y (NPY) and its receptors have been demonstrated to have anti-inflammative as well as antidepressant effects. In the present study, the ability of NPY to modulate depressive-like behaviors induced by lipopolysaccharides (LPS) in rats and the receptors and signaling mechanisms involved were investigated. Continuous injection LPS (i.p) for 4 days led to development of depressive-like behaviors in rats, accompanied with M1-type microglia activation and increased levels of IL-1β as well as decreased levels of NPY and Y2R expression in the mPFC selectively. Local injection of NPY into the medial prefrontal cortex (mPFC) ameliorated the depression-like behaviors and suppressed the NLRP3 inflammasome signaling pathway. Y2R agonist PYY (3-36) mimicked and Y2R antagonist BIIE0246 abolished the NPY effects in the mPFC. All these results suggest that NPY and Y2R in the mPFC are involved in the pathophysiology of depression and NPY plays an antidepressant role in the mPFC mainly via Y2R, which suppresses the NLRP3 signaling pathway, in LPS-induced depression model rats.